(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper analysis Sashi Deshpande’s female’ protagonists and the struggle of theirs to confirm thier identity in society. For the goal of this particular study, all her novels have been considered, but the thrust of the analysis is actually on 4 of her main novels viz., ‘The Dark Holds No Terrors’, ‘Roots and Shadows’, ‘That Long Silence’ and The Binding Vine. In this particular paper, an effort is actually, therefore, created by studying Shashi Deshpande’s female’ protagonists, as portrayed by her, with a view to recognize and appreciate their tribulations and trials under the effect of the conflicting influence of modernity and tradition.